Development and validation of an instrument to measure collaborative goal setting in the care of patients with diabetes. Issue 1 (20th February 2017) - Morris, Heather L; Dumenci, Levent; Lafata, Jennifer E
Abstract : Objective: Despite known benefits of patient-perceived collaborative goal setting, we have a limited ability to monitor this process in practice. We developed the Patient Measure of Collaborative Goal Setting (PM-CGS) to evaluate the use of collaborative goal setting from the patient's perspective. Research design and methods: A random sample of 400 patients aged 40 years or older, receiving diabetes care from the Virginia Commonwealth University Health System between 8/2012 and 8/2013, were mailed a survey containing potential PM-CGS items (n=44) as well as measures of patient demographics, perceived self-management competence, trust in their physician, and self-management behaviors. Confirmatory factor analysis was used to evaluate construct validity. External validity was evaluated via a structural equation model (SEM) that tested the association of the PM-CGS with self-management behaviors. The direct and two mediated (via trust and self-efficacy) pathways were tested. Results: A total of 259 patients responded to the survey (64% response rate), of which 192 were eligible for inclusion. Results from the factor analysis supported a 37-item measure of patient-perceived CGS spanning five domains: listen and learn; share ideas; caring relationship; measurable objective; and goal achievement support (χ=4366.13, p<0.001; RMSEA=0.08). Results from the SEM supported the external validity of the PM-CGS. The relationship between CGS and self-management was partially mediated by perceived competence (p<0.05). The direct effect between the PM-CGS and self-management was significant (p<0.001). Conclusions: CGS can be validly measured by the 37-item PM-CGS. Use of the PM-CGS can help illustrate actionable deficits in goal-setting discussions.